Drug Traffickers' Deaths: Criticisms of Laws not All Fair - MOHAN, S. Chandra (Institutional Knowledge at Singapore Management University, 2015)
This is a comment on the western media frenzy over the executions of eight drug traffickers in Indonesia. The commentary looks at whether the anguish over the executions following a conviction and appeals to higher courts in accordance with Indonesian law, apart fromn the loss of life,was well placed.